Does a presentation Media Influence the Evaluation of Consumer Products? A Comparative Study to Evaluate Virtual Reality, Virtual Reality with Passive Haptics and a Real Setting. - Galán, Julia; García García, Carlos; Felip, Francisco; Contero, Manuel (International Journal of Interactive Multimedia and Artificial Intelligence, 2021)
Technologies based on image offer a high potential to present consumers with products by focusing on their visual characteristics, but lack the capacity to physically interact with an object, which can compromise how consumer products are evaluated. The present study aims to analyse the influence of different presentation media on how users perceive the product by comparing the evaluation of a piece of furniture made by a sample of 203 users, which was presented in three different settings: a real setting (R), a Virtual Reality setting (VR) and a Virtual Reality with Passive Haptics setting (VRPH). To evaluate the product in the different settings, a semantic differential scale was built that comprised 12 bipolar pairs of adjectives. To study the results, the descriptive statistics for the semantic differential scales were analysed, a study about the frequency of repetition was conducted of each evaluation, a Kruskal-Wallis test was conducted and Dunn’s post hoc tests were performed. The results showed that the presentation media of a piece of furniture influenced the evaluation of how users perceived it. These results also revealed that the haptic interaction with a product influenced how users perceived it compared to an exclusively visual interaction.